Analysis of the Implementation of Pancasila Values in Citizenship Education Learning in Elementary Schools - Gustina, Nelsa (International Journal of Students Education, 2025)
Civic Education (PKn) learning in Elementary Schools has a strategic role in shaping the character of the younger generation based on Pancasila values. This study aims to determine the values of Pancasila in education, civic education (PKN), Implementation of Pancasila Values in Learning and the Role of Teachers in Pancasila Value-Based Learning. This literature uses Systematic Literature Reviews (SLR), Literature review is a research method that identifies, evaluates and interprets all relevant research results related to certain research questions, certain topics, or phenomena of concern. This literature uses Systematic Literature Reviews (SLR), which is a synthesis of systematic, clear, comprehensive literature studies , by identifying, analyzing, evaluating through the collection of existing data with explicit search methods and involving a critical review process in selecting studies. The results of the study show that Civic Education is a subject that aims to form intelligent, characterful, and responsible citizens. Through this learning, students are invited to understand the rights and obligations as citizens, Pancasila values, and attitudes that support unity and justice.